2003
DOI: 10.1023/a:1022855818944
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Overproduction of nitric oxide by inducible nitric oxide synthase (iNOS) acts cytotoxically and contributes to inflammation. We explored the roles of iNOS in the pathogenesis of Helicobacter pylori-associated diseases. Using reverse-transcribed PCR, we examined topographical patterns of iNOS mRNA expression in the gastroduodenal mucosa in H. pylori-negative controls and H. pylori-positive patients with duodenal ulcer (DU), gastric ulcer (GU), and ulcer-free gastritis. iNOS expression showed topographical varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Increased activity of iNOS and high levels of KC and IL-1β have been observed in the gastric mucosa of patients with chronic gastritis and gastric adenocarcinoma [46]. Neutrophil infiltration is positively correlated with the expression of iNOS and inflammatory cytokines in gastric mucosa [47]. These studies showed that the upregulation of iNOS, KC, and IL-1β by H. pylori infection might be associated with neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 72%
“…Increased activity of iNOS and high levels of KC and IL-1β have been observed in the gastric mucosa of patients with chronic gastritis and gastric adenocarcinoma [46]. Neutrophil infiltration is positively correlated with the expression of iNOS and inflammatory cytokines in gastric mucosa [47]. These studies showed that the upregulation of iNOS, KC, and IL-1β by H. pylori infection might be associated with neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 72%
“…In patients with gastritis, especially those infected with H. pylori , nitric oxide produced by inducible nitric oxide synthase(iNOS) and COX-2 is induced to regulate epithelial cell growth and inflammatory changes ( 84 ). Studies have underscored the significance of iNOS as an inflammation-inducing enzyme and a key contributing factor to gastritis ( 85 ). Furthermore, iNOS can bind to H. pylori and induce apoptosis in gastric mucosal.…”
Section: Inflammatory Molecules and Microorganisms Regulation In Gast...mentioning
confidence: 99%
“…Inflammatory conditions in the gastric mucosa are characterized by activation of NF-κ B, resulting in the expression of NF-κ B-regulated, inflammatory-inducible genes, such as inducible nitric oxide synthase (iNOS) and cyclo-oxygenase-2 (COX-2) [ 10 ]. Elevated expression of iNOS and increased nitric oxide synthesis are a hallmark of the inflammatory reaction in H. pylori -induced gastritis [ 12 ]. Studies have shown that a constitutive overproduction of iNOS and, hence, of nitric oxide may lead to DNA and protein damage, which could increase the risk of development of cancer [ 13 ].…”
Section: Introductionmentioning
confidence: 99%